Investigation of the sperm aquaporin molecules expression in fertile and infertile men (Annals of Medical Research, 2023)
Aim: Infertility is pregnancy failure for a year without protection, despite regular sexual intercourse. Various disorders and deficiencies in both genders can cause this situation, and a considerable portion of these cases consists of male infertility. We aimed to investigate the relationship between aquaporin molecules expressed in human sperm cells and male infertility.Materials and Methods: We carried out the study on the sperm cells of two different groups consisting of ten fertile and twenty infertile men older than eighteen. Smear slides were prepared following spermiogram testing. These slides were stained using the Diff-quick and immunohistochemistry protocols to test the Kruger strict sperm morphology and detect the immune expression of the AQP molecules, respectively.Results: The results of the spermiogram and Kruger-strict sperm morphology analysis showed that average sperm cell count and numerical sperm parameters values in the semen of infertile individuals decreased, and sperm counts with anomalies were higher in infertile ones versus those of fertile (p0.05).Conclusion: According to our findings, the immune expression of infertile ones' aquaporin molecules was reduced by a small amount, even if this was not statistically meaningful. These molecules of the sperm cells can not be primarily associated with male infertility. However, further advanced-level research is required on this issue to make a precise decision.
Keywords: Aquaporins; Fertile; Immune expression; Infertile; Sperm